2017
DOI: 10.1093/mnras/stx222
|View full text |Cite
|
Sign up to set email alerts
|

Production of complex organic molecules:H-atom addition versus UV irradiation

Abstract: AB S TRAC TComplex organic molecules (COMs) have been identified in different environments in starforming regions. Laboratory studies show that COMs form in the solid state, on icy grains, typically following a 'non-energetic' (atom-addition) or 'energetic' (UV-photon absorption) trigger. So far, such studies have been largely performed for single processes. Here, we present the first work that quantitatively investigates both the relative importance and the cumulative effect of '(non-)energetic' processing. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 88 publications
3
48
2
Order By: Relevance
“…We also assumed a depletion of F and Cl by a factor 100 with respect to the solar value. We find that the abundance of methyl formate (with respect to H 2 ) in the high temperature regime (100-300 K) varies between ∼7 × 10 −10 and ∼2.5 × 10 −8 once the temperature is above 100 K. Rivilla et al (2017) Even if our simulations predict abundances of methyl formate relatively similar to the observations with just the inclusion of the gas phase mechanism, it was also shown that methyl formate could also form on the grains with ethylene glycol and glycolaldehyde through hydrogenation of CO:H 2 CO:CH 3 OH ice mixtures under certain conditions (Chuang et al 2016;Chuang et al 2017). Running the previous cases after the inclusion of this grain surface mechanism is beyond the scope of this paper.…”
Section: Inclusion Of Methyl Formate Grain Surface Formation Pathwaysupporting
confidence: 60%
“…We also assumed a depletion of F and Cl by a factor 100 with respect to the solar value. We find that the abundance of methyl formate (with respect to H 2 ) in the high temperature regime (100-300 K) varies between ∼7 × 10 −10 and ∼2.5 × 10 −8 once the temperature is above 100 K. Rivilla et al (2017) Even if our simulations predict abundances of methyl formate relatively similar to the observations with just the inclusion of the gas phase mechanism, it was also shown that methyl formate could also form on the grains with ethylene glycol and glycolaldehyde through hydrogenation of CO:H 2 CO:CH 3 OH ice mixtures under certain conditions (Chuang et al 2016;Chuang et al 2017). Running the previous cases after the inclusion of this grain surface mechanism is beyond the scope of this paper.…”
Section: Inclusion Of Methyl Formate Grain Surface Formation Pathwaysupporting
confidence: 60%
“…It is generally accepted that chemical processes in the bulk and on the surface of interstellar ices are essential in facilitating the formation of both rather simple species such as H 2 O 4,5 and CH 3 OH 6 and more complex species, including small sugars and alcohol sugars like glycolaldehyde and glycerol. [7][8][9][10][11][12][13] Laboratory experiments, indeed, confirmed that a) Electronic mail: kofman@strw.leidenuniv.nl molecular complexity in an ice environment can be enhanced through (radiation-induced) radical recombinations, 14,15 atom addition and abstraction reactions, 13,16,17 or upon thermally induced processes during warm-up. [18][19][20][21] Alternatively, larger species such as polycyclic aromatic hydrocarbons (PAHs), typically formed in the ejecta of dying stars, may also directly freeze out onto icy grains.…”
Section: Introductionmentioning
confidence: 75%
“…Numerous efforts have been done in the last years to understand how COMs are formed in the insterstellar medium (ISM), by combining observations (e.g., Belloche et al 2009;Jørgensen et al 2016;Martín-Doménech et al 2017;Codella et al 2017;Rivilla et al 2017a,b), chemical modeling (e.g., Garrod et al 2008;Vasyunin & Herbst 2013a,b;Balucani et al 2015;Taquet et al 2016;Vasyunin et al 2017;Coutens et al 2018;Bergantini et al 2018;Quénard et al 2018a), and laboratory experiments (e.g. Fedoseev et al 2015;Chuang et al 2016Chuang et al , 2017. However, despite all efforts, our understanding about the synthesis of COMs in the ISM is still very limited.…”
Section: Introductionmentioning
confidence: 99%